2022
DOI: 10.1007/s10549-022-06528-0
|View full text |Cite
|
Sign up to set email alerts
|

Post-diagnostic beta blocker use and breast cancer-specific mortality: a population-based cohort study

Abstract: Purpose Beta blockers (BB) have been associated with improved, worsened, or unchanged breast cancer outcomes in previous studies. This study examines the association between the post-diagnostic use of BBs and death from breast cancer in a large, representative sample of New Zealand (NZ) women with breast cancer. Methods Women diagnosed with a first primary breast cancer between 2007 and 2016 were identified from four population-based regional NZ breast can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…2–6 weeks) [ 43 , 44 ]. As evidenced by Supplementary Table 3, those who took statins in the lowest dose categories generally had a shorter median time to death/last follow up than those with took statins in the higher dose categories (a similar phenomenon was evidenced in a previous paper of ours for beta blockers [ 81 ]). Therefore, the slightly higher HRs observed in the 0–3 month and 3–6 month dose categories may in fact be an artefact of women in these dose categories being dispensed statins towards the end of their life.…”
Section: Discussionsupporting
confidence: 81%
“…2–6 weeks) [ 43 , 44 ]. As evidenced by Supplementary Table 3, those who took statins in the lowest dose categories generally had a shorter median time to death/last follow up than those with took statins in the higher dose categories (a similar phenomenon was evidenced in a previous paper of ours for beta blockers [ 81 ]). Therefore, the slightly higher HRs observed in the 0–3 month and 3–6 month dose categories may in fact be an artefact of women in these dose categories being dispensed statins towards the end of their life.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, a meta-analysis of studies published between 2010 and 2013 found that women with breast cancer who took beta blockers had a significantly decreased risk of breast cancer death than women with breast cancer who did not take beta blockers [ 20 ]. A recent meta-analysis of nearly 15,000 New Zealand breast cancer patients saw a short term—over 3 months—increased risk of death among patients who took beta blockers post-diagnosis, and a protective effect with long-term use [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Propranolol is currently being studied as single administration adjuvant therapy or in combination with standard therapies in several clinical trials (57). Statin use was first found associated with improved outcomes in colorectal cancer patients in 2005 (58) and subsequent studies confirmed this observation and extend to postdiagnosis statin use (59)(60)(61)(62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%